Bioeconomic analysis of squid fisheries in the Karangantu fishing port of Banten Province - Hafidz Zulghaffar Zain; Ririn Irnawati; Dini Surilayani (Jurnal Perikanan dan Kelautan, 2022)
Squid is one of the catches of fisheries favored by the community and one of the fisheries commodities with high economic value. In 2017 the squid production in the Karangantu archipelago fisheries port reached 328 tons or 14.3% of the total capture fisheries production, which reached 2,293 tons. All Squid that enters the market come entirely from catches in nature (sea); if you only rely on the effort of catching it alone, one day, there may be overfishing. This study aimed to determine the optimal level of Squid (Loligo sp.) Resource management is based on biological and economic aspects in the Karangantu PPN. The study was conducted from April to May 2019. Retrieval of primary data and secondary data funds. The research procedure consisted of calculating CPUE (Catch Per Unit Effort), MSY (Maximum Sustainable Yield), and MEY (Maximum Economic Yield) using primary data and secondary data obtained from Karangantu. The calculation of bioeconomic analysis using the Gordon-Schaefer model showed that the highest profit value was in the MEY condition of 234,423 kg/year and 2,622 trips/year with a gain of Rp. 2,901,811,197. Based on the Fox model, the utilization rate of Squid (Loligo sp.) It is 129% and is in the status of over exploited.